THE PRODUCTION OF ENGLISH CONSONANTS /θ/ AND /ð/ BY ENGLISH DEPARTMENT STUDENTS - Diah Merrita (STBA LIA - Jakarta, 2021)
Indonesians have been taking much concern in English since it has been applied in formal education curricula. Also, not all Indonesians are familiar with English pronunciation, especially its characteristics in phonemes. Some English consonants even do not exist in Indonesian consonants such as the sounds /θ/ and /ð/ categorized as voiceless and voiced interdental fricatives. Due to this concern, this study investigates the production of English voiced and voiceless interdental consonants uttered by English Department students as non-native speakers of English using the Praat application. There were eight undergraduate first-year English major students as the respondents. The researcher gave them eighteen words consisting of /θ/ and /ð/ sounds in initial, medial, and final word-position. The data are in audio recordings. The result revealed that most students changed the voiced interdental fricative into consonants such as /d/ and /t/. This inappropriate way also happened when they produced voiceless interdental fricatives. They changed /θ/ sound into consonant sounds such as /d/ and /t/.